Pengaruh Residu Pemberian Abu Vulkanis Gunung Agung dan Pupuk Kompos terhadap Tanah dan Tanaman Kacang Tanah (Arachis hypogaea L.) - NARKA, I WAYAN; ARTHAGAMA, I DEWA MADE; ATMAJA, I WAYAN DANA (Agrotrop : Journal on Agriculture Science; Vol 12 No 2 (2022)DO - 10.24843/AJoAS.2022.v12.i02.p05, 2022)
Residual Effect of Mount Agung Volcanic Ash and Compost on Soil and Peanut Plants ( Arachis hypogaea L.).   Research on the application of Mount Agung volcanic ash and compost has been carried out with cowpea as an indicator plant, but volcanic ash has not shown any effect. The volcanic ash of Mount Agung is in the form of material that has not been weathered, so to accelerate weathering it is necessary to add organic matter . The purpose of this study was to determine the residual effect of giving volcanic ash and compost on soil and peanut plant. The design used was a factorial randomized block design with 3 replications. The volcanic ash factor consists of 3 levels, namely A0 = no volcanic ash, A1 = 10% volcanic ash and A2 = 30% volcanic ash. The compost factor consists of 3 levels, namely K0 = without compost, K1 = 10 tons of compost ha -1 , and K2 = 20 tons of compost ha -1 .  Parameters of soil properties observed were : total porosity, nitrogen, phosphorus and potassium content and C-organic matter content. Observation of peanut plants included : plant height, number of pods, weight of oven-dried pods, weight of oven-dried seeds and weight of oven-dried peanut stem. The results of research showed that there was no interaction between the treatment of volcanic ash residue and compost residue on the soil and peanut plants, while the single treatment of compost residue had a significant effect on peanut plants. The treatment of volcanic ash residue has not shown a significant effect, both on the soil and on peanut plants.